ANALISIS PERLAKUAN AKUNTANSI DAN PENGALOKASIAN BIAYA LINGKUNGAN PADA PT ASPEX KUMBONG - - Hermiyetti; Griffit Yoyner Dondokambey (Universitas Trunojoyo Madura, 2012)
PT Aspex Kumbong is one of manufacture companies producing paper for news. In it production activity, besides producing paper for news, it also generating liquid and solid waste as it byproducts. Therefore, PT Aspex Kumbong do the environmental management activities to realize company commitment to the environment.Some of the environmental management activities done by PT Aspex Kumbong are: Wash Water Treatment (WWT), solid waste management, quality control of waste, and testing the quality of environment. These activities generate environmental costs. The environmental costs are then being analyzed to determine its accounting treatment and allocation. Some of the environmental costs of PT Aspex Kumbong are allocated in production cost as overhead cost and some of the costs are allocated in the general and administration cost as maintenance and repair costs. The result of comparing to the PSAK 33 as the theory suggests that the accounting treatment and alocation of environmental costs of PT Aspex Kumbong is not in accordance with the PSAK 33. It is suggested that to determine the environmental cost per unit of PT Aspex Kumbong, the company needs to use the amount of emission generated. The environmental management activity reporting is very useful to internal management as an instrument for environmental decision-making and as a public communication tool.